Training of Posyandu Cadres in the Preparation of Local Food-Based MP-ASI for Stunting Prevention in Nolokla Village, East Sentani - Nuburi, Dorci; Lusiana, Sanya Anda; Deda, Margaretha Oktofina (Sarana Ilmu Indonesia (salnesia), 2025)
Based on the 2022 Indonesian Nutritional Status Survey, the prevalence of stunted toddlers in Papua remained high at 34,6%, with Jayapura Regency specifically recording a rate of 20,2%. This issue needed to be addressed seriously in order to accelerate the reduction of stunting. Providing an appropriate modified MP-ASI (complementary feeding) formula was associated with improving the nutritional status of toddlers. MP-ASI could also be subsidized with local food sources, supporting the government’s efforts in diversifying food consumption. Posyandu cadres required training in preparing MP-ASI using local food ingredients to assist mothers of toddlers in providing balanced and nutritious meals. The purpose of this community service activity was to conduct training and mentoring for Posyandu cadres in Nolokla Village, East Sentani District, on how to produce MP-ASI. The community service design employed a community-based participatory approach using lectures, group discussions, and hands-on practice. The training was conducted over the course of one day, using tilapia fish and kepok bananas as main ingredients, processed into biscuits. A total of seven cadres from Posyandu Maleo 1 participated in the activity. This activity was implemented from May to November 2024. The results demonstrated an improvement in both the knowledge and skills of the cadres, with pre-test scores increasing by 15 points after the intervention. The training effectively enhanced the cadres’ ability to process MP-ASI from local food ingredients and is expected to become a sustainable, community-based intervention for stunting prevention.